Predilection for developing a hematogenous orthopaedic implant-associated infection in older versus younger mice - John M. Thompson; Alyssa G. Ashbaugh; Yu Wang; Robert J. Miller; Julie E. Pickett; Daniel L. J. Thorek; Robert S. Sterling; Lloyd S. Miller (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background The pathogenesis of hematogenous orthopaedic implant-associated infections (HOIAI) remains largely unknown, with little understanding of the influence of the physis on bacterial seeding. Since the growth velocity in the physis of long bones decreases during aging, we sought to evaluate the role of the physis on influencing the development of Staphylococcus aureus HOIAI in a mouse model comparing younger versus older mice. Methods In a mouse model of HOIAI, a sterile Kirschner wire was inserted retrograde into the distal femur of younger (5–8-week-old) and older (14–21-week-old) mice. After a 3-week convalescent period, a bioluminescent Staphylococcus aureus strain was inoculated intravenously. Bacterial dissemination to operative and non-operative legs was monitored longitudinally in vivo for 4 weeks, followed by ex vivo bacterial enumeration and X-ray analysis. Results In vivo bioluminescence imaging and ex vivo CFU enumeration of the bone/joint tissue demonstrated that older mice had a strong predilection for developing a hematogenous infection in the operative legs but not the non-operative legs. In contrast, this predilection was less apparent in younger mice as the infection occurred at a similar rate in both the operative and non-operative legs. X-ray imaging revealed that the operative legs of younger mice had decreased femoral length, likely due to the surgical and/or infectious insult to the more active physis, which was not observed in older mice. Both age groups demonstrated substantial reactive bone changes in the operative leg due to infection. Conclusions The presence of an implant was an important determinant for developing a hematogenous orthopaedic infection in older but not younger mice, whereas younger mice had a similar predilection for developing periarticular infection whether or not an implant was present. On a clinical scale, diagnosing HOIAI may be difficult particularly in at-risk patients with limited examination or other data points. Understanding the influence of age on developing HOIAI may guide clinical surveillance and decision-making in at-risk patients.